Biomechanical design of a new percutaneous locked plate for comminuted proximal tibia fractures. (June 2022) - Djuricic, Aleksandar; Gee, Aaron; Schemitsch, Emil H.; Quenneville, Cheryl E.; Zdero, Radovan
Highlights: A new proximal tibia fracture plate was designed with semi-rigid materials. Knee load mimicked toe-touch weight-bearing right after tibia repair surgery. The design criterion was controlled axial interfragmentary motion for early healing. Stiffness, bone stress, implant stress, and interfragmentary motion were computed. Results were compared to traditional steel and titanium plates. Abstract: Comminuted proximal tibia fractures are an ongoing surgical challenge. This "proof of concept" study is the first step in designing a new percutaneous plate for this injury under toe-touch weight-bearing as prescribed after surgery. Finite element simulations generated design curves for overall stiffness, bone and implant stress, and interfragmentary motion using 3 fixations (no, 1, or 2 "kickstand" (KS) screws across the fracture gap) over a range of plate elastic moduli (EP  = 5 to 200 GPa). Combining well-established optimization criteria to enhance callus formation (i.e. 0.2 mm ≤ axial interfragmentary motion ≤ 1 mm; shear / axial interfragmentary motion ratio < 1.6), lessen stress shielding (i.e. bone stress under the proposed plate > bone stress under a traditional titanium or steel plate), and reduce steel screw breakage (i.e. screw max stress < ultimate tensile stress of steel) resulted in plate design recommendations: 172.6 ≤ EP < 200 GPa (no KS screw), 79.8 ≤ EP < 100 GPa (1 KS screw), and 4.9 ≤ EP < 100 GPa (2 KS screws). A prototype plate could be made from materials currently used or proposed for orthopaedics, such as polymers, fiber-reinforced polymers, fiber metal laminates, metal foams, or shape memory alloys.